2020
DOI: 10.1021/acs.jafc.9b07868
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Translocation of Triflumezopyrim in Rice Plants

Abstract: A new type of mesoionic insecticide triflumezopyrim is mainly used to control rice planthoppers, leafhoppers, etc. In order to study the uptake and translocation characteristics of this new insecticide in rice (Oryza sativa), a method for the detection of triflumezopyrim in rice, soil, and water was established using liquid–liquid extraction and QuEChERS sample pretreatment combined with liquid chromatography–triple quadrupole tandem mass spectrometry. The distribution of triflumezopyrim in rice was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…The current study showed that the inoculation of bacterial consortium can have a detoxification effect on M. sativa in soil and water. , The obtained result is consistent with Bhatt et al who showed that the inhibitory effect of the added chlorsulfuron-methyl on PH and FW of Zea mays L. disappeared and PH and FW recovered to 83.9 and 83.1%, respectively after inoculation with Enterobacter sp. CE-1.…”
Section: Resultssupporting
confidence: 91%
“…The current study showed that the inoculation of bacterial consortium can have a detoxification effect on M. sativa in soil and water. , The obtained result is consistent with Bhatt et al who showed that the inhibitory effect of the added chlorsulfuron-methyl on PH and FW of Zea mays L. disappeared and PH and FW recovered to 83.9 and 83.1%, respectively after inoculation with Enterobacter sp. CE-1.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, these two pesticides remain in the cell wall. 33 These experimental results also provide a reasonable explanation as to how that pymetrozine is transported to the aerial part, whereas spirotetramat is mainly stored in the root.…”
Section: Distribution Of Spirotetramat and Pymetrozine Insupporting
confidence: 58%
“…Determination of TFM in rice stem or grain followed the methods of Peng et al . and Fan et al 36,37 . UPLC analysis was performed with an Agilent 1290 UPLC system equipped with a binary pump, automatic sampler, column oven, and diode array detector.…”
Section: Methodsmentioning
confidence: 99%
“…Standard triflumezopyrim was provided by Jiangsu Agroproduct Quality Test Center (Jiangsu Academy of Agricultural Sciences). Determination of TFM in rice stem or grain followed the methods of Peng et al and Fan et al 36,37 UPLC analysis was performed with an Agilent 1290 UPLC system equipped with a binary pump, automatic sampler, column oven, and diode array detector. A 1-μl aliquot of the sample solution was injected into an Agilent Eclipse Plus chromatographic column C 18 (2.1 × 50 mm i.d., 1.7 μm).…”
Section: Lc-ms/ms Methods For the Determination Of Tfm In The Rice Stem And Grainmentioning
confidence: 99%